TALABALARǴA BILIM BERIWDE INFORMACIYALÍQ TEXNOLOGIYALARDÍŃ ROLI - Ótepbergenov, J.S. (SCIENCE and SOCIETY, 2021)
The article reflects the scientific analysis of the interpretation of the topic by students using information technology, with a graphic image and smart cards.